Adjunct Publication of the 28th ACM Conference on User Modeling, Adaptation and Personalization 2020
DOI: 10.1145/3386392.3397596
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Adaptation Based on Students' Dyslexia Type: An Empirical Evaluation of Students' Satisfaction

Abstract: Where a licence is displayed above, please note the terms and conditions of the licence govern your use of this document. When citing, please reference the published version. Take down policy While the University of Birmingham exercises care and attention in making items available there are rare occasions when an item has been uploaded in error or has been deemed to be commercially or otherwise sensitive.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2
2
1

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…This experiment showed that learners with dyslexia were more satisfied when adapting learning material according to their reading skill level. This is in line with a previous study [3]. The system interface was identical between the two conditions, but the interface component in the ELS was rated more highly in the adaptive condition, as well as the learning and system personalization components.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This experiment showed that learners with dyslexia were more satisfied when adapting learning material according to their reading skill level. This is in line with a previous study [3]. The system interface was identical between the two conditions, but the interface component in the ELS was rated more highly in the adaptive condition, as well as the learning and system personalization components.…”
Section: Discussionsupporting
confidence: 91%
“…In terms of adaptivity, Alghabban et al [3] investigated how personalizing learning material based on dyslexia type affects children's satisfaction. An adaptive e-learning system was implemented to help children in elementary schools to practice their reading skill.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…These limitations include a lack of interactivity, of learner control of the environment, of adaptive presentation formats, of learning navigation and of personalisation of educational materials. From this perspective, contextualising learning serves as a new paradigm for adaptive e-learning systems, which aims to solve these traditional limitations (Alghabban and Hendley 2020b). A system's ability to adjust its output in response to learner needs is often referred to as adaptivity or adaptation (Brusilovsky 2001).…”
Section: Introductionmentioning
confidence: 99%
“…dyslexia) by considering their characteristics within an educational environment. For learners with dyslexia, characteristics such as their dyslexia type and their knowledge level are significant factors influencing their learning (Benmarrakchi et al 2017b;Alghabban and Hendley 2020b). These can be incorporated into the learning environment to drive the personalisation of the learning experience.…”
Section: Introductionmentioning
confidence: 99%